ANALISIS KRITIS TERHADAP PENEGAKAN HUKUM PASAL 273 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - MOHAMMAD RONI MUSTOFA, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2012)
AbstractThis thesis is studies of Straightening of law to Section 273 Law Number, 2009 About Traffic And Road Transportation. By the legal and social legal reseach method, obtained conclusion that : 1. Straightening of law to Section 273 Law Number, 2009, still be not able yet to be executed effectively, because : a. Arrangement un-clarity of meaning